Treatment-free remission after dasatinib in patients with chronic myeloid leukaemia in chronic phase with deep molecular response: final 5-year analysis of DASFREE: original paper - Shah, Neil P.; García-Gutiérrez, Valentín; Jiménez-Velasco, Antonio; Larson, Sarah M.; Saußele, Susanne; Rea, Delphine; Mahon, François-Xavier; Levy, Moshe Yair; Gómez-Casares, María Teresa; Mauro, Michael J.; Sy, Oumar; Martin-Regueira, Patricia; et al. (British journal of haematology, 2023)
Patients with chronic myeloid leukaemia in chronic phase (CML-CP) who have a sustained deep molecular response (DMR) are eligible to discontinue treatment and attempt treatment-free remission (TFR). In the DASFREE study (ClinicalTrials.gov; NCT01850004), the 2-year TFR rate after dasatinib discontinuation was 46%; here we present the 5-year update. Patients with a stable DMR after ≥2 years of dasatinib therapy discontinued treatment and were followed for 5 years. At a minimum follow-up of 60 months, in 84 patients discontinuing dasatinib, the 5-year TFR rate was 44% (n = 37). No relapses occurred after month 39 and all evaluable patients who relapsed and restarted dasatinib (n = 46) regained a major molecular response in a median of 1.9 months. The most common adverse event during the off-treatment period was arthralgia (18%, 15/84); a total of 15 withdrawal events were reported in nine patients (11%). At the 5-year final follow-up, almost half of the patients who discontinued dasatinib after a sustained DMR maintained TFR. All evaluable patients who experienced a relapse quickly regained a DMR after restarting dasatinib, demonstrating that dasatinib discontinuation is a viable and potentially long-term option in patients with CML-CP. The safety profile is consistent with the previous report.
Online veröffentlicht: 29. Mai 2023
Gesehen am 29.02.2024